Management Pendidikan Abad 21, Globalisasi, Teknologi - Eem Merani Destiana; Dimas Sartika; Nur Puspitasari; Asiyah Asiyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the role and strategies of educational management amidst global dynamics and the development of information technology. The method used is a qualitative approach through literature review of various relevant scientific sources, focusing on the development of educational management in the digital era. The results show that 21st-century educational management must be innovative, flexible, and technology-based. Additionally, strengthening 4C competencies (critical thinking, creativity, collaboration, and communication) is a key focus in the development of adaptive and effective learning systems. The role of technology in education is not only as a tool but also as an integral part of modern educational governance, supporting both the learning process and the overall management of education. Key challenges faced include the readiness of human resources, the equal distribution of technological infrastructure, and the digital divide between regions and social groups. Therefore, adaptive and visionary managerial strategies are essential to creating an excellent and sustainable educational system. The implementation of policies supporting the integration of technology into education and the development of competencies for educators is a crucial step to ensure the achievement of inclusive and quality education. This study is expected to serve as a reference in the development of sustainable educational management policies and practices, as well as enhance the quality of education in the digital era.